A Study of Job Satisfaction in Relation to Participation and Alienation - Hossein Afrasiab; Behnam Jamshidi Solokloo; Hossein Ghodrati (جامعه شناسی کاربردی, 2013)
Introduction With increasing social activities of organizations and their role in development of societies, the studies about organization function are expanded in behavioral and social sciences. Many studies and researchers every year investigate job satisfaction as a crucial aspect of organizations around the world. This attention is rooted in the important role of human resources in organizational success and plans. This attitude leads to some evolutions in management, by focusing on participatory management, and on employees' motivations and behaviors. At this round, job satisfaction is a more important variable. Job satisfaction has entered in most of the studies about jobs and organizations, in the last decades and attracted researchers and employees alike. But other variables should be investigated along with job satisfaction. Participation in job and organizational decision making, is a more crucial variable for satisfaction at work. Participation and sense of participation, can affect employees' job satisfaction directly and indirectly. Although participation in job tasks and decisions has effects on job satisfaction, other consequences are also important. One of them is alienation. Participation in job and organization can promote sense of belonging and decrease alienation from self, others and organization. This study has investigated the relationship between job satisfaction and participation by considering the alienation as an intermediate variable.